Arts Education - Erita Lee Acham Chen (The Journal of Intelligence, Conflict and Warfare, 2021)
On April 23, 2021, Erita Lee Acham Chen presented Arts Education: An Unexpected Tool in the Quest for a Safer World at the 2021 CASIS Generation Z Congress. The presentation was followed by a moderated question and answer period. Key points of discussion included the current situation for township youths in South Africa, how performing arts non-governmental organizations (NGO) have provided vulnerable youths with a safe place, and how the skills learned in these programs have had a positive impact on their lives.